Can you get a pure surd when you find the difference of two surds
Answers
Answered by
1
Answer:
Yes
Explanation:
we can find a Pure surd by adding two surds but the surds to be added must be same.
For Example:
√a + √a=2 √a
The answer here is not in pure form but it can be converted into pure form as shown below.
2 √a= √(2.2) √a = √(2.2a)= √(4a) Because √(2.2) = 2
So we also come to know that a Mixed Surd can be converted into Pure Surd and vice versa.
Similar questions
Chemistry,
7 months ago
Social Sciences,
7 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Physics,
1 year ago